The Draghi Government put to the Test by the National Recovery and Resilience Plan. Issue 4 (2nd October 2022) - Di Mascio, Fabrizio; Natalini, Alessandro; Profeti, Stefania
ABSTRACT: The political and institutional trajectory of Italy was clearly punctuated by the economic upheavals of the pandemic. The articles in the special issue aim to assess the character of the institutional change prompted by the economic response to the pandemic, and in particular by the National Recovery and Resilience Plan (NRRP), in different policy areas. Three contributions analyse the reform dynamics related to the strategic axis of the Italian NRRP, namely digitalization and innovation (Ottone and Barbieri), the ecological transition (Cotta and Domorenok), and social inclusion as concerns labour-market policies (Tassinari). Two contributions focus on two overarching priorities of the NRRP: gender equality (Donà) and development of southern Italy (Cerruto, Cersosimo and Raniolo). Finally, one contribution focuses on reform of the public administration, which has been identified as a key area, affecting horizontally all missions in the NRRP (Di Mascio, Natalini and Profeti). Overall, the articles in the special issue highlight that the pandemic has been followed by a process of institutional change that occurred both incrementally and unevenly, often disguising substantial continuity.